MORFOMETRIK DAN MERISTIK IKAN BUNTAL MAS (Tetraodon fluviatilis H.B.) DI MUARA PERAIRAN BENGKALIS PROVINSI RIAU - Tri Setia Ningsih; Roza Elvyra; Yusfiati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Morphometric and meristic analysis of pufferfish (Tetraodon fluviatilis H.B.) in estuary of Bengkalisconducted in April-August 2014, which aims to determine the characteristics morphometric andmeristik pufferfish (T. fluviatilis H.B.) in three different habitats. This study used the method of direct data collection sampling from study sites. Sampling was carried out at three different stations are three i.e Pakning River, Bengkel River Station and the Jangkang River with 30 male and 30 female. The results showed morphometric characters pufferfish gold female and male on the Pakning River greater than the Bengkel River and Jangkang River with status allometric growth is positive, negative allometric and isometric. The results showed of morphometric analysis pufferfish (T. fluviatilis H.B.) using T-test showed a significant difference in the pufferfish gold male and female at each study site. Analysis of meristik pufferfish gold male and female at each study site showed a significant difference.